ANALISIS CAMPUR KODE YANG DIGUNAKAN DALAM MEMBACAKAN PESAN SINGKAT DARI PENDENGAR RADIO RIS FM: KAJIAN SOSIOLINGUISTIK - Tepu Sitepu; Nurul Wahidah (Jurnal Riset Rumpun Ilmu Bahasa, 2022)
Generally, people use the everyday language that they apply in their surrounding environment and it is not uncommon for the use of Indonesian to be tucked into their native language and foreign languages. This research only focuses on finding and determining the amount of code mixing used when reading short messages by broadcasters from RIS FM radio listeners. According to Suardi, there are 3 types of code mixing, namely inner code mixing, outer code mixing and hybrid code mixing. This research is a literature study so it does not require a special location for the research. This study aims to identify and describe the use of code mixing in the reading of short messages by broadcasters from RIS FM radio listeners. Based on the research results obtained from the tape recorder and notes, it was found that there was internal code mixing, external code mixing, and mixed code mixing in the form of words and sentences.